Migration characteristics as a prognostic factor in cerebral sparganosis. (April 2022) - Feng, Li; Jiao, Xiao; Zeng, Chang; Zhao, Charlie W.; Li, Rong; Zhang, Leiyao; Yang, Zhuanyi; Liao, Weihua; Liu, Dingyang; Xiao, Bo; Yang, Zhiquan
Highlights: Migration modes were correlated with clinical outcomes. The worm was prone to migrate toward the cortical surface after medication. Lesions distal from the original site may represent a delayed immune reaction. ABSTRACT: Objective: To differentiate diagnostic and prognostic factors from the clinical material of patients with cerebral sparganosis in central South China. Methods: Consecutive patients with cerebral sparganosis from our hospital between 2010 and 2018 were retrospectively enrolled. The clinical manifestations, radiographic features, treatment, and outcomes of these patients were analyzed. Results: Thirty patients with cerebral sparganosis were included, and foci migration on magnetic resonance imaging was detected in 22 patients, from whom we observed 4 migration modes: interlobar migration (50.0%, 11/22); transmidline migration (27.3%, 6/22); transventricular migration (13.6%, 3/22); and cerebellum-brainstem migration (9.1%, 2/22). The percentage of good outcomes was higher in patients with live worm capture than in those without live worm capture (75.0%, 12/16 vs 33.3%, 2/6). Exposure to preoperative antiparasitic medication was associated with worm migration toward the cortical surface, which led to a higher probability of live worm capture. Conclusions: We propose 4 modes of sparganosis migration that are correlated with worm capture and neurologic prognosis. We found that exposure to antiparasitic medication was associated with worm migration toward the cortical surface, leading to a higher probability of live worm capture. These observations suggest a novel significance for preoperative medication of cerebral sparganosis.